Benthic biofilm controls on fine particle dynamics in streams. Issue 1 (11th January 2017) - Roche, K. R.; Drummond, J. D.; Boano, F.; Packman, A. I.; Battin, T. J.; Hunter, W. R.
Abstract: Benthic (streambed) biofilms metabolize a substantial fraction of particulate organic matter and nutrient inputs to streams. These microbial communities comprise a significant proportion of overall biomass in headwater streams, and they present a primary control on the transformation and export of labile organic carbon. Biofilm growth has been linked to enhanced fine particle deposition and retention, a feedback that confers a distinct advantage for the acquisition and utilization of energy sources. We quantified the influence of biofilm structure on fine particle deposition and resuspension in experimental stream mesocosms. Biofilms were grown in identical 3 m recirculating flumes over periods of 18–47 days to obtain a range of biofilm characteristics. Fluorescent, 8 µm particles were introduced to each flume, and their concentrations in the water column were monitored over a 30 min period. We measured particle concentrations using a flow cytometer and mesoscale (10 µm to 1 cm) biofilm structure using optical coherence tomography. Particle deposition‐resuspension dynamics were determined by fitting results to a stochastic mobile‐immobile model, which showed that retention timescales for particles within the biofilm‐covered streambeds followed a power‐law residence time distribution. Particle retention times increased with biofilm areal coverage, biofilm roughness, and mean biofilm height. Our findings suggest that biofilm structural parameters are key predictors of particle retention in streams and rivers. Key Points: We quantified biofilm‐particle interactions by fitting a stochastic mobile‐immobile model to observations from laboratory flume experiments Fine particle retention was positively correlated with biofilm height, roughness, and streambed coverage Results can be integrated within the stochastic mobile‐immobile framework to assess the effects of biofilms on fine particle dynamics